3-Aminopropylphosphinic acid--a potent, selective GABAB receptor agonist in the guinea-pig ileum and rat anococcygeus muscle. - Hills, J. M. (1989)
1. 3-Aminopropylphosphinic acid, a gamma-aminobutyric acid (GABA) analogue, was tested for activity on guinea-pig isolated ileum and rat isolated anococcygeus muscle preparations. The effects of 3-aminopropylphosphinic acid were compared with those of GABA and baclofen. 2. In the electrically stimulated ileum, 3-aminopropylphosphinic acid, like GABA and baclofen, caused a concentration-dependent inhibition of the cholinergic twitch contraction, the IC50 value being 1.84 +/- 0.23 microM (n = 12). Unlike GABA, but like baclofen, 3-aminopropylphosphinic acid did not produce an initial contraction. 3. The inhibitory effects of 3-aminopropylphosphinic acid and baclofen in the guinea-pig ileum were not significantly antagonized by bicuculline (10 microM), phentolamine plus propranolol (both 1 microM), yohimbine (1 microM), naloxone (1 microM), impromidine (1 microM) or 8-phenyltheophylline (10 microM). The inhibitory effects of 3-aminopropylphosphinic acid, but not of baclofen, were however antagonized by phaclofen (500 microM). In addition the effects of 3-aminopropylphosphinic acid were abolished by baclofen desensitization in the guinea-pig ileum. 4. 3-Aminopropylphosphinic acid, GABA and baclofen reduced the twitch contraction evoked by electrical field stimulation in the rat anococcygeus muscle. The IC50 for 3-aminopropylphosphinic acid inhibition of the anococcygeus contraction was 0.89 +/- 0.15 microM (n = 8). 5. It is concluded that 3-aminopropylphosphinic acid is a potent, selective GABAB agonist, being seven times more potent than baclofen in the guinea-pig ileum and five times more potent than baclofen in the rat anococcygues muscle preparations.